Thymosin beta 10 is a key regulator of tumorigenesis and metastasis and a novel serum marker in breast cancer. Issue 1 (December 2017) - Zhang, Xin; Ren, Dong; Guo, Ling; Wang, Lan; Wu, Shu; Lin, Chuyong; Ye, Liping; Zhu, Jinrong; Li, Jun; Song, Libing; Lin, Huanxin; He, Zhenyu
Abstract Background Thymosin beta 10 (TMSB10) has been demonstrated to be involved in the malignant process of many cancers. The purpose of this study was to determine the biological roles and clinical significance of TMSB10 in breast cancer and to identify whether TMSB10 might be used as a serum marker for the diagnosis of breast cancer. Methods TMSB10 expression was evaluated by immunohistochemical analysis (IHC) of 253 breast tumors and ELISA of serum from 80 patients with breast cancer. Statistical analysis was performed to explore the correlation between TMSB10 expression and clinicopathological features in breast cancer. Univariate and multivariate Cox regression analysis were performed to examine the association between TMSB10 expression and overall survival and metastatic status. In vitro and in vivo assays were performed to assess the biological roles of TMSB10 in breast cancer. Western blotting and luciferase assays were examined to identify the underlying pathway involved in the tumor-promoting role of TMSB10. Results We found TMSB10 was upregulated in breast cancer cells and tissues. Univariate and multivariate analysis demonstrated that high TMSB10 expression significantly correlated with clinicopathological features, poor prognosis and distant metastases in patients with breast cancer. Overexpression of TMSB10 promotes, while silencing of TMSB10 inhibits, proliferation, invasion and migration of breast cancer cells in vitro and in vivo. Our results further reveal that TMSB10 promotes the proliferation, invasion and migration of breast cancer cells via AKT/FOXO signaling, which is antagonized by the AKT kinase inhibitor perifosine. Importantly, the expression of TMSB10 is significantly elevated in the serum of patients with breast cancer and is positively associated with clinical stages of breast cancer. Conclusion TMSB10 may hold promise as a minimally invasive serum cancer biomarker for the diagnosis of breast cancer and a potential therapeutic target which will facilitate the development of a novel therapeutic strategy against breast cancer.